Search for charged Higgs bosons in decays of top quarks in pp collisions at square root s = 1.96 TeV. - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We report on the first direct search for charged Higgs bosons decaying into cs in tt events produced by pp collisions at square root s = 1.96 TeV. The search uses a data sample corresponding to an integrated luminosity of 2.2 fb(-1) collected by the CDF II detector at Fermilab and looks for a resonance in the invariant mass distribution of two jets in the lepton + jets sample of tt candidates. We observe no evidence of charged Higgs bosons in top quark decays. Hence, 95% upper limits on the top quark decay branching ratio are placed at B(t --> H(+)b)< 0.1 to 0.3 for charged Higgs boson masses of 60 to 150 GeV/c(2) assuming B(H(+) --> cs)=1.0. The upper limits on B(t --> H(+)b) are also used as model-independent limits on the decay branching ratio of top quarks to generic scalar charged bosons beyond the standard model.